2023
DOI: 10.1039/d3py00381g
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the network architecture of thiol–ene photo-crosslinked poly(ε-caprolactone) towards tailorable materials for light-based 3D-printing

Abstract: Thiol–ene photo-crosslinked poly-ε-caprolactone networks, exhibiting varying network architectures, were employed to fine-tune physico-chemical characteristics, while simultaneously exploring their potential application in digital light processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Several of the photo-cross-linked hydrogels developed cracks during deformation. We hypothesize that the potential of homophotopolymerization of the PEG-Alkyne chains and the possibility of double addition of thiol to alkyne in the photo-cross-linked gels leads to excess/unreacted thiol chains and less regularity/homogeneity in the cross-linking process . This translates into a reduction of the mechanical integrity (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the photo-cross-linked hydrogels developed cracks during deformation. We hypothesize that the potential of homophotopolymerization of the PEG-Alkyne chains and the possibility of double addition of thiol to alkyne in the photo-cross-linked gels leads to excess/unreacted thiol chains and less regularity/homogeneity in the cross-linking process . This translates into a reduction of the mechanical integrity (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that the potential of homophotopolymerization of the PEG-Alkyne chains and the possibility of double addition of thiol to alkyne in the photocross-linked gels leads to excess/unreacted thiol chains and less regularity/homogeneity in the cross-linking process. 52 This translates into a reduction of the mechanical integrity (see Figure 1). Premature collapse may result from these inhomogeneities acting as stress concentration zones.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Quaak et al studied tunable thiol− ene networks with telechelic, trifunctional, and tetra-functional PCL, which were degradable with sodium hydroxide (NaOH) aqueous solutions. 23 Takasu et al reported several linear thiol− ene polymers synthesized from malic acid, tartaric acid, and dianhydro sugars, which showed varied degrees of biodegradation through biochemical oxygen demand (BOD) tests. 24−26 It is worth noting that biodegradable hydrogels and nanoparticles have also been demonstrated, for which the biodegradation is conducted in enzymatic aqueous solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thijssen et al utilized dialkene functionalized poly­(ε-caprolactone) to create biocompatible 3D-printed materials and demonstrated their degradation in PBS . Quaak et al studied tunable thiol–ene networks with telechelic, trifunctional, and tetra-functional PCL, which were degradable with sodium hydroxide (NaOH) aqueous solutions . Takasu et al reported several linear thiol–ene polymers synthesized from malic acid, tartaric acid, and dianhydro sugars, which showed varied degrees of biodegradation through biochemical oxygen demand (BOD) tests. It is worth noting that biodegradable hydrogels and nanoparticles have also been demonstrated, for which the biodegradation is conducted in enzymatic aqueous solutions. , These works demonstrate the effectiveness of thiol–ene systems in incorporating degradable linkages to design degradable polymers, but studies on soil compostability of thiol–ene cross-linked, network photopolymers have not been conducted.…”
Section: Introductionmentioning
confidence: 99%